The history of sound [videorecording (DVD)] - Mescal, Paul, 1996-; O'Connor, Josh; Cooper, Chris (Mubi, 2025)
Two young music students, Lionel and David, attending the Boston Conservatory in 1917, bond over their shared love of folk music. They reconnect a few years later, embarking on a song collecting trip in the backwaters of Maine.